Discussion on the switching between type-2 fuzzy sets and intuitionistic fuzzy sets: An application in medical diagnosis. Issue 2 (17th February 2018) - Kumar, Kamesh; Pandey, D.
Abstract: Uncertainty in real life problems has become fruitful modeling business for fuzzy sets and generalized fuzzy sets. Various attempts have been made to apply theory of these sets to reduce the uncertainty from such problems. Own proposed a switching relation between type-2 fuzzy sets and intuitionistic fuzzy sets and applied it to the medical diagnosis. In this paper, some conceptual deficiencies are pointed out in the switching. After removing these, an improved version of the switching relation is proposed and some propositions related to the switching are proved. Finally, an algorithm is developed to reflect the applicability of the switch in medical diagnosis and a hypothetical example is discussed to illustrate the proposed algorithm.